2016
DOI: 10.3233/jad-160188
|View full text |Cite
|
Sign up to set email alerts
|

EEG Dominant Frequency Peak Differentiates Between Alzheimer’s Disease and Frontotemporal Lobar Degeneration

Abstract: We investigated the power of EEG as biomarker in differential diagnosis of Alzheimer's disease (AD) and frontotemporal lobar degeneration (FTLD). EEG was recorded from 106 patients with AD or FTLD, of which 37 had a definite diagnosis, and 40 controls. Dominant frequency peaks were extracted for all 19 channels, for each subject. The average frequency of the largest dominant frequency peaks (maxpeak) was significantly lower in AD than FTLD patients and controls. Based on ROC analysis, classification could be m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 25 publications
5
25
0
Order By: Relevance
“…https://doi.org/10.1101/19009316 doi: medRxiv preprint adding the EEG parameters, which are slightly behind on their own. We observed the same effect of increased accuracy in the definite group in our previous study focussing on EEG (Goossens et al, 2017 . CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Classificationsupporting
confidence: 85%
See 2 more Smart Citations
“…https://doi.org/10.1101/19009316 doi: medRxiv preprint adding the EEG parameters, which are slightly behind on their own. We observed the same effect of increased accuracy in the definite group in our previous study focussing on EEG (Goossens et al, 2017 . CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Classificationsupporting
confidence: 85%
“…To reduce redundancy, balance the number of neurochemical and EEG features and deal with the fact that some channels did not always exhibit peaks, we summarised the peaks found over all channels into four regions. To do this, we fine-tuned the algorithm from our previous study (Goossens et al, 2017) to detect the DFP with the highest amplitude over the channels within a specific region, as defined in table 2. This procedure was also helpful in avoiding missing data, as only one channel per region needed to show a clearly distinguishable peak.…”
Section: Dominant Frequency Peak Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis revealed that there is currently insufficient evidence to recommend the use of SPECT scans in routine practice [28]. EEG may be helpful [29][30][31] but it is not usually employed in a dementia clinic.…”
Section: The Variability and Inaccuracy Of The Diagnostic Criteriamentioning
confidence: 99%
“…Furthermore, Van der Meer et al found a decrease in upper-alpha power (10–12 Hz) and an increase in lower-alpha power (8–10 Hz), which may relate to the slowing of the alpha-peak in Alzheimer's dementia (Goossens et al, 2017). Functional connectivity studies have observed an increase in functional connectivity in the beta band [assessed by the phase lag index (Tewarie et al, 2013), and synchronization likelihood (Schoonheim et al, 2013)] and the functional connectivity in the beta band correlated with an overall cognitive score (Tewarie et al, 2013).…”
Section: Neurophysiologymentioning
confidence: 99%